A study of cavitating and non-cavitating performances of valveless micropump through dynamic measurement of chamber pressure. (4th February 2015) - Chandrasekaran, Arvind; Packirisamy, Muthukumaran
Abstract: A lot of work has gone into the study of valveless micropumps for various applications. However, the complex fluid-structure interactional physics and associated phenomena such as cavitation affects the characterization of valveless micropumps, for applying them reliably in any real-time applications. This paper presents a method of characterization of valveless micropump performance through dynamic measurement of chamber pressure. Experimental investigation has been carried out to study the micropump behavior through pressure measurement under both cavitation and non-cavitation conditions, and the results show that this technique is useful for the characterization of micropump.